The development and differentiation of callus fennel plant (Riznayj) Foeniculum vulgare (Mill) and the formation of whole plants - Abd Al-Nuaime; Seham Mahmood; Mura AL-Katib (College of Education for Pure Sciences, 2006)
This study carried out the induction of callus from the explants (leaves, stems and roots) of the medicinal plants Foeniculum vulgare Mill (Fennel) by using MS medium which contained different concentration of growth regulators of Naphthalene acetic acid and Benzyl adenine (NAA + BA) or Indole acetic acid and Kinetine (NAA + Kin). The results indicated that solid MS medium with 1.0 mg/L from each of NAA and BA was the best for the induction and growth of callus. The callus of the explants used were amenable to regenerate and produce numerous shoots. Leaf callus gave the highest percentage of regeneration, then callus of stems and roots. Also, the' results showed the one step regeneration occured for all the callus in the MS medium, especially, MS medium contained (NAA 1.0 mg/L + BA 1.0 mg/L). The regenerants were rooted in MS medium contained 1.0 mg/L of NAA or 2,4-D.